2021
DOI: 10.1186/s13578-021-00553-0
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of AREG for bleomycin-induced skin fibrosis

Abstract: We report our discovery of an important player in the development of skin fibrosis, a hallmark of scleroderma. Scleroderma is a fibrotic disease, affecting 70,000 to 150,000 Americans. Fibrosis is a pathological wound healing process that produces an excessive extracellular matrix to interfere with normal organ function. Fibrosis contributes to nearly half of human mortality. Scleroderma has heterogeneous phenotypes, unpredictable outcomes, no validated biomarkers, and no effective treatment. Thus, strategies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that IL-17 can promote inflammation and cancer development by inducing the production of factors such as CXCL5 71 . AREG can be secret by various cells, which can cause the proliferation and differentiation of fibroblasts and protect pulmonary tissue by activating the EGFR signaling pathway to inhibit TNF-α and mediating the apoptotic signaling pathway to reduce damage to alveolar epithelial cells 72 , 73 . Previous studies have reported that AREG, a target gene of IL-17, promotes the development of keratin-forming cell proliferation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that IL-17 can promote inflammation and cancer development by inducing the production of factors such as CXCL5 71 . AREG can be secret by various cells, which can cause the proliferation and differentiation of fibroblasts and protect pulmonary tissue by activating the EGFR signaling pathway to inhibit TNF-α and mediating the apoptotic signaling pathway to reduce damage to alveolar epithelial cells 72 , 73 . Previous studies have reported that AREG, a target gene of IL-17, promotes the development of keratin-forming cell proliferation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…We then asked whether there was a specific marker expression pattern associated with IL1B / IL23A -coexpressing cells, and found that they were characterized by CD83 , an activation marker for DCs ( Zhou and Tedder, 1995 ), AREG and EREG associated with fibrosis ( Zhang et al, 2021 ), and the receptors for glucose and lipids, OLR1 and SLC2A3 ( Yu et al, 2010 ; Fig. 6 f ).…”
Section: Resultsmentioning
confidence: 99%
“…[37] It upregulates fibrosis, a pathological wound healing process, during the development of bleomycin-induced cutaneous fibrosis and is associated with elevated cell proliferation in the dermis. [38] CDKN1A and ATF3 may be involved in the progression of POP through multiple pathways. The progression of POP is closely related to apoptosis, [39] DNA repair, [8] autophagy, [40] and the onset of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…[37] It upregulates fibrosis, a pathological wound healing process, during the development of bleomycin-induced cutaneous fibrosis and is associated with elevated cell proliferation in the dermis. [38]…”
Section: Discussionmentioning
confidence: 99%